Young rural–urban migrant fathers in China: everyday 'China Dream' and the negotiation of masculinity. Issue 3 (3rd July 2019) - Lin, Xiaodong
ABSTRACT: Drawing upon a study on rural–urban migrant young men at a delivery company in a southern Chinese city, I examine how they make sense of their private life as fathers. Situated within the pervasive national discourse of the 'China Dream' in which individual aspiration for a better life is advocated in line with the prosperity of the nation marked by neoliberal modernization, the paper seeks to understand how the marginalized urban working-class young men make sense of their subjectivities through a gender lens. In particular, I investigate the process of masculine identification in the young migrant fathers' narratives. It highlights the way the young men negotiate ordinary masculine ideals and familial practices of modern fatherhood, desiring a better future for the next generation. I explore how they navigate through the constraints of material inequalities (i.e. as urban working class) and the tension with their gender responsibilities/expectations within a wider familial context, in making sense of their gender subjectivities.